Kontekstualisasi Teologi Pentakosta dalam Perintisan Gereja pada Masyarakat Marapu Sumba - Wesley Mokar; Gidion Gidion (STT Kristus Alfa Omega, 2026)
This research aims to design church planting guidelines that are contextual to Sumba culture based on Pentecostal doctrine in Bethel Tabernacle Church (GBT) East Sumba Region. This research is useful as a practical reference for church planters in integrating local cultural values and the teachings of Pentecostal theology. The method used is a combination with the Sequential Exploratory model, which begins with the collection and analysis of qualitative data, followed by quantitative data. The type of research is level 1 research and development, focused on product design development. The results of the study resulted in the design of church planting guidelines in four main subjects: cultural approaches, Pentecostal doctrine, church planting strategies, and implementation of Sumba culture. The novelty of this research lies in the contextualization of Sumba culture and Pentecostal theology in the form of written guidelines that are applicable to church planting ministries